Managerial Ownership as a Moderator of Financial Performance and Capital Structure in Enhancing Firm Value - Marshal Attarik, Muhammad; Puspitasari, Diana; Nur Chasanah, Amalia; Jati Kusuma, Pradana (Journal Economic Business Innovation, 2026)
Purpose—This study investigates the joint and conditional effects of financial performance and capital structure on firm value, while critically examining the moderating role of managerial ownership within an emerging market context. Design/methodology/approach—Grounded in agency theory and signaling theory, this study employs a quantitative panel data approach to examine the interplay between profitability, leverage, and firm valuation. Financial performance is proxied by Return on Assets (ROA), capital structure by Debt to Equity Ratio (DER), and firm value by Price to Book Value (PBV). Advanced panel regression techniques are utilized to capture both direct and moderating effects. Findings—The findings demonstrate that financial performance exerts a strong and statistically significant positive influence on firm value, underscoring its role as a credible signal of managerial efficiency and future growth prospects. In contrast, capital structure shows a negative yet statistically insignificant relationship, indicating that the market does not consistently price leverage. Notably, managerial ownership fails to moderate these relationships, suggesting that ownership alignment alone is insufficient to effectively resolve agency conflicts or enhance valuation outcomes. Originality/value—This study challenges the conventional governance assumption that managerial ownership universally strengthens firm value. By revealing its limited moderating role, the study provides a refined perspective on the boundaries of agency alignment mechanisms. It highlights the contextual limitations of internal governance structures in shaping market perceptions. Implications—The results emphasize the importance of strengthening fundamental performance indicators and credible signaling mechanisms rather than relying on ownership structures. Firms and policymakers should prioritize transparency, efficiency, and broader governance quality to sustain firm value and investor confidence.